Neuropsychological Outcomes in Patients with Complicated Versus Uncomplicated Mild Traumatic Brain Injury: 6-Month Follow-Up - Veeramuthu, Vigneswaran; Narayanan, Vairavan; Ramli, Norlisah; Hernowo, Aditya Tri; Waran, Vicknes; Bondi, Mark W.; Delano-Wood, Lisa; Ganesan, Dharmendra (Elsevier, 2017)
Objective To compare the extent of persistent neuropsychological impairment in patients with complicated mild traumatic brain injury (mTBI) and those with uncomplicated mTBI. Methods Sixty-one patients with mTBI (Glasgow Coma Scale score 13–15) were recruited prospectively, categorized according to baseline computed tomography findings, and subjected to neuropsychological assessment at initial admission (n = 61) as well as at a 6-month follow-up (n = 30). The paired t test, Cohen's d effect size calculation, and repeated-measures analysis of variance were used to establish the differences between the 2 groups in terms of neuropsychological performance. Results A trend toward poorer neuropsychological performance among the patients with complicated mTBI was observed during admission; however, performance in this group improved over time. In contrast, the uncomplicated mTBI group showed slower recovery, especially in tasks of memory, visuospatial processing, and executive functions, at follow-up. Conclusions Our findings suggest that despite the broad umbrella designation of mTBI, the current classification schemes of injury severity for mild neurotrauma should be revisited. They also raise questions about the clinical relevance of both traumatic focal lesions and the absence of visible traumatic lesions on brain imaging studies in patients with milder forms of head trauma.